Can Associative Effects Affect In Vitro Digestibility Estimates Using Artificial Fermenters? - Larissa Frota Camacho; Tadeu Eder da Silva; Marcia de Oliveira Franco; Edenio Detmann (Ruminants, 2023)
We aimed to test the associative effects among forages, and between forage and concentrates on the in vitro digestibility of dry matter and neutral detergent fibre using an artificial ruminal fermentation system. The study consisted of two assays, in which associative effects were evaluated among three forages, sugarcane, maize silage, and Tifton 85 hay under two incubation conditions (single feed or all feeds together in a jar), and the associative effects between sugarcane and soybean meal and/or ground maize. For the first assay, sugarcane digestibility increased (p < 0.02), whereas the maize silage digestibility decreased (p < 0.01) when forages were incubated together in the same jar. Tifton hay digestibility was not altered (p ≥ 0.57) by the incubation condition. In the second assay, the sugarcane digestibility was depressed (p < 0.05) when the forage was incubated along with maize grain. For both assays, the pattern of repeatability for digestibility estimates presented an influence of the incubation condition. We concluded that the incubation of different feeds together in the same jar using artificial fermenters causes associative effects among them. These effects can influence the estimates of in vitro dry matter and fibre digestibility and alter their repeatability.